Susceptibility of eucalypt taxa to a natural infestation by Leptocybe invasa - da Silva, Paulo Henrique Müller [UNESP]; Junqueira, Luis Renato; de Araujo, Marcio José [UNESP]; Wilcken, Carlos Frederico [UNESP]; Moraes, Mario Luiz Teixeira [UNESP]; de Paula, Rinaldo Cesar [UNESP] (Springer Nature, 2020)
Recently, pest occurrence in forest plantations has been increasing influenced by genotypes and environmental conditions such as climate change, thus impacting production negatively. In 2008, the exotic pest Leptocybe invasa (Hym: Eulophidae), known as the blue gum chalcid, was introduced in Brazil causing damage to eucalypt plantations in many regions of the country. To this end, this study evaluated the susceptibility of Eucalyptus camaldulensis (one seedlot), E. grandis (four seedlots), E. urophylla (four seedlots), and the “E. urograndis” hybrid (E. urophylla × E. grandis) (three seedlots) exposed to a natural infestation by L. invasa in two seasons (winter and summer). The attack on seedlings was classified in terms of severity as healthy (no pest attack), oviposition (only oviposition signs) and gall formation. The results show a significant higher pest incidence in summer compared to winter. Further, Eucalyptus urophylla was the least attacked and 90% of the seedlings were healthy whereas E. grandis showed the highest number of seedlings with galls. The E. urograndis hybrid showed intermediate results between the two species. Differences in susceptibility were observed between seedlots within species. Eucalyptus camaldulensis, which was expected to have the highest incidence of galls, had a high oviposition incidence (60%) and low gall incidence (< 10%), probably due to its provenance. The susceptibility of the different eucalypt families varied significantly with respect to L. invasa infestation, and family heritability ranged from 0.27 to 0.68. The genetic control of L. invasa is possible through the selection of tolerant and resistant material, considering the species, provenance, and family.
Keywords: Blue gum chalcid; Environmental conditions; Exotic pest; Heritability